Vannamei (Litopenaeus vannamei) Frozen Shrimp Raw Material Inventory Management With Supply Chain Management Approach - Iid Mufaidah; Tartila Fitri; Sony Swasono; Yuli Wibowo (Department of Social Economy, Faculty of Agriculture , University of Brawijaya, 2023)
Raw material inventory is one of the most expensive assets of the company, especially at national private companies in Banyuwangi is developing a frozen vannamei shrimp agro-industry with PND commercial products (Peeled and Devained). Companies often experience problems with losing sales profits if export demand tends to increase, because companies have not maximized their inventory management. So by using a three-level supply chain management approach, namely the level of finished products, the level of processing and the level of raw materials, it is important to ensure the availability of finished products at any time. Through this approach, the average amount of raw material needed for production of each PND product is PND 26/30 of 12,333.33 kg/month, 31/40 of 75,416.67 kg/month, 41/50. 28,750 kg/month, 51/60 42,250 kg/month, 61/70 21,083.33 kg/month, and 71/90 11,083.33 kg/month. so that the company's service level for PND finished products is above 100%, which is an average of 111,39%.